Russia's "impressionable years" and Putin's inheritance - Michael V. Alexeev; William Pyle; Jiaan Wang (EconPol Forum, 2023)
In Russia, where the early transition's economic pain was not alleviated by the same emotive high of 'liberation and independence' experienced elsewhere in post-communist Europe, the drop in support for liberal economic and political values was comparatively steep and enduring. Evidence from the Integrated Values Survey (a combination of the World Values Survey and the European Values Study) demonstrates that Russians de-prioritized democratic freedoms and increased their support for an interventionist state in the economy between 1990 and 1995. The "values gap" that grew dramatically in the early 1990s between Russians and post-communist citizens elsewhere in Europe has persisted through the most recent wave of the Integrated Values Survey. This pattern - a "values gap" that opened in the early 1990s and persisted to the present day - is observable among men, women, and across different age cohorts. Within Russia, the degree to which regions' electoral support for Boris Yeltsin dropped between the 1991 and 1996 presidential elections explains more illiberal attitudes in the most recent wave of the Integrated Values Survey.
Keywords: 330